2014
DOI: 10.1111/wrr.12231
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous curcumin efficacy on healing and scar formation in rabbit ear wounds under nonischemic, ischemic, and ischemia–reperfusion conditions

Abstract: Curcumin, a spice found in turmeric, is widely used in alternative medicine for its purported anti-inflammatory and antioxidant activities. The goal of this study was to test the curcumin efficacy on rabbit ear wounds under nonischemic, ischemic, and ischemia-reperfusion conditions. Previously described models were utilized in 58 New Zealand White rabbits. Immediately before wounding, rabbits were given intravenous crude or pure curcumin (6 μg/kg, 30 μg/kg, or 60 μg/kg) dissolved in 1% ethanol. Specimens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…) indicated that the initial migration of cells was faster in the HC and LC groups than in the blank and control groups. This might be a consequence of the constant release of curcumin in the HC and LC groups, in agreement with published observations that curcumin considerably improves granulation in non‐ischemic wounds …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…) indicated that the initial migration of cells was faster in the HC and LC groups than in the blank and control groups. This might be a consequence of the constant release of curcumin in the HC and LC groups, in agreement with published observations that curcumin considerably improves granulation in non‐ischemic wounds …”
Section: Discussionsupporting
confidence: 92%
“…This might be a consequence of the constant release of curcumin in the HC and LC groups, in agreement with published observations that curcumin considerably improves granulation in non-ischemic wounds. 60 A series of important events takes place at the edge of the wound, accompanying granulation. Epidermal cells in the direct vicinity of the edge of the wound begin to thicken within the first 24-48 h post injury.…”
Section: Discussionmentioning
confidence: 99%
“…33 Briefly, 4 or 6 full-thickness dermal punches 7 mm in diameter were made on the ventral surface of the ear down to but not including the perichondrium. The cartilage was scored around the circumference of the wound to allow for histomorphometric analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Several histomorphometric measurements were determined using a digital image analysis system (NIS-Elements Basic Research, Nikon Corporation, Kanagawa, Japan) at 2× and 10× magnification as previously described. 33 Each parameter was measured in a blind manner. Scar elevation index (SEI) was calculated to quantify the extent of hypertrophic scarring in the scarring model.…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin was found to suppress TGF-β1/SMAD pathway and extra cellular matrix (ECM) production in primary keloid fibroblasts and reduce pro-inflammatory cytokines, interleukins (IL-1β, IL-6, and IL-8), which directly decrease hypertrophic scarring [20]. …”
Section: Introductionmentioning
confidence: 99%